HIV-related plasmablastic lymphoma causing extensive bone destruction in the mandible - Kayahara, Giseli Mitsuy [UNESP]; Valente, Vitor Bonetti [UNESP]; Salzedas, Leda Maria Pescinini [UNESP]; Passador-Santos, Fabrício; Furuse, Cristiane [UNESP]; Biasoli, Éder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Bernabé, Daniel Galera [UNESP] (Elsevier, 2022)
Plasmablastic lymphoma (PBL) is a rare subtype of large B-cell lymphoma commonly associated with HIV infection. HIV-related PBL has a dismal prognosis. The aggressive clinical course of the disease may lead to the development of rapid-growing swellings, like several benign and malignant conditions. Herein, we reported the case of a 38-year-old woman with a painful swelling in the mandible initially diagnosed as an abscess derived from a tooth extraction. Intraoral examination revealed a painful swelling with reddish, white and purplish areas in the posterior region of the mandible without signs of infection. Imaging exams showed an extensive bone destruction in the left mandibular body. Histopathological examination revealed a high proliferation of plasmacytoid cells with nuclear hyperchromatism. Tumor cells were negative for CD20, and positive for Ki-67, CD138, IgG and lambda chain. The diagnosis of oral PBL was defined and serological test showed positivity for HIV. Eight months after starting treatment, the patient died due to complications of cancer treatment. Lymphoproliferative malignancies related to HIV infection should be included in the differential diagnosis of rapid-growing swellings in the oral cavity.
Keywords: Bone lesions; Cancer; Diagnosis; HIV; Lymphoma; Lymphoproliferative malignancies; Malignant tumor; Non-Hodking's lymphoma; Oral plasmablastic lymphoma; Plasmablastic lymphoma